Pengembangan Produk UMKM di Desa Waringin Jaya - Sri Wahyuningsih; Ari MH; Andi Suhandi; Azmy MH; De Euis Fitria (LPPM STEBIS YPII, 2024)
Community service is an activity with a number of studies that place lecturers among village communities and invite lecturers to think critically so that the way to socialize and increase their capacity by involving the community in the local area. Lecturers are faced with various challenges in implementing activity programs both individually and in groups. These challenges make community service a new experience for lecturers, as well as a place to train the abilities and skills of lecturers related to social interests. The involvement of lecturers in the local area to improve the economy of the community in the village with various creations and innovations of food that can be traded so as to provide benefits to the local community. With this community service program, it can be beneficial for people who have a business soul by socializing the manufacture and development of squid chili sauce and spring roll chips food innovations.